VAT compliance cost for SMEs in Algeria - Ferdjani, Mohamed Abdessadek (2015)
Every organization tries to maximize its earnings by stringent cost control measures; however, only some costs are controllable, i.e., material, labor, etc., while others are not, i.e., taxes. In a country like Algeria, the overall tax rate is up to 30% for corporations, and these corporations, on average, spend 451 hours/year on tax compliance. Such a huge amount of time is spent for compliance due to the complex and ever-changing nature of the tax structure in Algeria. As SMEs are the main economic drivers for the Algerian economy, these SMEs are responsible for around 60% of Algerian‘s gross domestic product and employ 1.86 million people. This study is an attempt to explore the VAT compliance cost for the SMEs operating in the Adrar State of Algeria. For this purpose, 360 questionnaires were distributed among SMEs operating in the Adrar State of Algeria, and 327 fully completed questionnaires were received. Descriptive statistics and cross-tabulation were applied to extract useful information. The researcher found that out of the 327, only 122 firms hire external advisors for tax compliance; of the 122 firms (38.3%) which hire external experts, they either utilize the services of different accounting firms or individual consultants. In addition, firms in Algeria spend 4,165,000 DZD in terms of external compliance cost. On the other hand, accounting and tax department‘s employees of sample SMEs, on average, spend 24,244 hours, for accounting and tax matters only. Out of the total hours, the value is 2,967,313 DZD (22.48%). Similarly, SMEs based on different categories (number of employees, number of years established and turnover) unanimously report that high tax compliance cost is significant and an extra burden on the company‘s earnings, which might discourage investors investing in SMEs, which are vital sources of employment and revenue